Quantification of egg ovalbumin hydrolysate-derived anti-hypertensive peptides in an in vitro model combining luminal digestion with intestinal Caco-2 cell transport. (September 2017) - Grootaert, Charlotte; Jacobs, Griet; Matthijs, Bea; Pitart, Judit; Baggerman, Geert; Possemiers, Sam; Van der Saag, Hans; Smagghe, Guy; Van Camp, John; Voorspoels, Stefan
Abstract: Food-derived peptides can impact blood pressure through several mechanisms. However, their fate in the gastro-intestinal tract and bioavailability are difficult to assess because of their fast degradation and challenging analysis in physiologically relevant matrices. The aim of this study was to construct an in vitro bioavailability methodology in which luminal digestion is combined with Caco-2 cell transport. Egg ovalbumin hydrolysate, both in pure form and mixed with a food matrix, was used as a test case. Results indicate that a food matrix protected bioactive peptides from luminal digestion, especially in small intestine. Moreover, the Caco-2 absorption peak was extended over a longer time period (> 60 min) compared to the pure peptide solutions (~ 15 min) which in total resulted in a 3–12 times higher absorption of the bioactive sequences after 60 min compared to fasted conditions. These results suggest further investigation is warranted towards peptide-based functional foods with improved gastro-intestinal stability and longer-term release in the blood. Graphical abstract: Highlights: A gut digestion/enterocyte absorption model was constructed to study egg albumen hydrolysate. Analytical methods allowed to quantify low amounts of specific peptides as inherent to the models. Digestive enzyme presence and food matrix strongly affect intestinal bioactive peptide integrity. This screening model may be used for development of slow-release peptide-based functional foods.